MEDICAL URGENCE IN THE LEARNING PROCESS - Samad Umarella M. Sahrawi Saimima Saddam Husein (al-Iltizam: Jurnal Pendidikan Agama Islam, 2018)
Abstract: In the process of learning media is a very important part in creating activeness of students. The existence of media, also very helpful for teachers in the learning process, especially helps in efforts to convey information to the recipient of the message in this case the students or students. In general, the distribution of learning media can be classified into three types, namely, audio, visual and audio-visual media. In the operational process of learning the three types of media experience development in accordance with the needs of the learning process that will be developed by the teacher or teaching staff. The selection and determination of the right learning media will make the media more urgent to use. Key Words: Urgency of Media, Learning Process